2015
DOI: 10.1155/2015/485709
|View full text |Cite
|
Sign up to set email alerts
|

Cholinergic Synaptic Transmissions Were Altered after Single Sevoflurane Exposure inDrosophilaPupa

Abstract: Purpose. Sevoflurane, one of the most used general anesthetics, is widely used in clinical practice all over the world. Previous studies indicated that sevoflurane could induce neuron apoptosis and neural deficit causing query in the safety of anesthesia using sevoflurane. The present study was designed to investigate the effects of sevoflurane on electrophysiology in Drosophila pupa whose excitatory neurotransmitter is acetylcholine early after sevoflurane exposure using whole brain recording technique. Metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…Sevoflurane has a wide range of effects on voltage-dependent ion channels ( Yokoyama et al, 2011 ; Liu Y. et al, 2016 ; Fukushima et al, 2020 ). Chen et al (2015) suggested that exposure to sevoflurane could reduce the transmission of cholinergic synapses by inhibiting the Ca 2+ current. Furthermore, Silva et al (2005) proposed that sevoflurane could promote the release of ACh in the cerebral cortex of rats by releasing Ca 2+ .…”
Section: Sevoflurane-inhalation Anesthesia and Pocdmentioning
confidence: 99%
“…Sevoflurane has a wide range of effects on voltage-dependent ion channels ( Yokoyama et al, 2011 ; Liu Y. et al, 2016 ; Fukushima et al, 2020 ). Chen et al (2015) suggested that exposure to sevoflurane could reduce the transmission of cholinergic synapses by inhibiting the Ca 2+ current. Furthermore, Silva et al (2005) proposed that sevoflurane could promote the release of ACh in the cerebral cortex of rats by releasing Ca 2+ .…”
Section: Sevoflurane-inhalation Anesthesia and Pocdmentioning
confidence: 99%
“…It has been reported that the clinical concentration of sevoflurane can inhibit ACh release in a dose-dependent manner (Shichino et al, 1998). Furthermore, an experiment by Chen et al (2015) in Drosophila melanogaster showed that 1, 2, and 3% sevoflurane for 24 h reduced presynaptic cholinergic neurotransmission, partially by inhibiting calcium current. Interestingly, the in vitro study by Naruo et al (2005) demonstrated that a clinically relevant sevoflurane concentration (i.e., 0.5-3%) inhibited the postsynaptic cholinergic neurotransmitters without the influence of presynaptic exocytosis or endocytosis, which instead functioned by nAChR blocking on the postsynaptic neuron.…”
Section: Modulation Of Cholinergic Synaptic Transmissionmentioning
confidence: 98%
“…Although the mechanism of neurotoxicity of sevoflurane is not completely clear, many studies have shown that the pathogenesis of sevoflurane-induced cognitive impairment may be related to neuroinflammation [ 6–8 ]. Recent studies have suggested that sevoflurane causes neuroinflammation by activating microglia [ 9 ] and peripheral immune cells, destroying the permeability of the blood–brain barrier [ 10 ], decreasing gut microbiota [ 11 ] and modulating cholinergic synaptic transmission, which can lead to cognitive impairment [ 12 ]. The hippocampus, a center for learning and memory, robustly expresses IL-1β receptor, which play key roles in learning and memory as pro-inflammatory factor receptors.…”
Section: Introductionmentioning
confidence: 99%